2019
DOI: 10.6000/2292-2598.2019.07.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Social Issues of People with Special Needs in Modern Mass Media

Abstract: This research paper discusses the problem of social issues, especially the issues of people with intellectual disabilities and how modern mass media supports. Mainly one case study was represented from aspects working with people with ID. This study aimed to examine how the press represents people with intellectual disabilities and how it helps people with this problem. The study was conducted using the method of qualitative content analysis. The material for the report consisted of research. The survey covere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hadley Cantril's Self-Anchoring Striving Scale (1965) is an example of one type of well-being assessment. At the same time, research has revealed that measurement of well-being is multifaceted, including a continuum from judgments of life (life evaluation) to feelings (daily effect) [25,26]. Different measures of well-being provide different perspectives on the process by which respondents reflect on or experience their lives.…”
Section: Methodsmentioning
confidence: 99%
“…Hadley Cantril's Self-Anchoring Striving Scale (1965) is an example of one type of well-being assessment. At the same time, research has revealed that measurement of well-being is multifaceted, including a continuum from judgments of life (life evaluation) to feelings (daily effect) [25,26]. Different measures of well-being provide different perspectives on the process by which respondents reflect on or experience their lives.…”
Section: Methodsmentioning
confidence: 99%